(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Innovation and adaptation are strategic aspects in maintaining the sustainability and relevance of Islamic educational institutions amid global social, technological, and economic changes. This study aims to analyse and evaluate the concepts and practices of innovation and adaptation in Islamic education management, both from theoretical and empirical perspectives. The research method used is a qualitative study based on library research with a conceptual analysis and content analysis approach to relevant primary and secondary sources, including books and national journal articles. The data were analysed to identify the principles of innovation and adaptation that are in line with Islamic values. The results of the study show that, from an Islamic perspective, innovation (tajdid) is not merely understood as technical renewal, but as a renewal of values based on tawhid, while adaptation (takyif) is understood as the ability of institutions to adjust to change without neglecting the principles of sharia. The integration of the values of tawhid, shura, and maslahah in management practices enables Islamic educational institutions to combine modern creativity with classical spirituality. Thus, innovation and adaptation based on Islamic values play an important role in realising productive, ethical, and falah-oriented (worldly and spiritual happiness) Islamic education management.